Assistance for Marketing Communication Strategy to Increase Revenue Generating for Indonesian MSMEs Upcycle Project - Masnia Ningsih; Atika Isnaining Dyah; Nurdiana Fitri Isnaini (Jurnal Soeropati)
Upcycle Project Indonesia is a Micro, Small and Medium Enterprise (MSMEs) that focuses on jeans waste management to support environmental issues in Indonesia. Despite having creative ideas and interesting concepts, Upcycle Project Indonesia faces various challenges in its development process, namely problems with production quality and marketing management. The purpose of this mentoring activity is to strengthen Upcycle Project Indonesia's unique product, so that it can compete nationally and internationally. The activity method used is the Participatory Rural Appraisal approach with active community participation. Through this community service program, we succeeded in helping Upject to be more productive and expand its marketing reach by providing support in the form of production equipment to produce higher quality products, marketing communication strategy management assistance and also the application of technology in the form of a Businness Model Canvas map which has an impact on increasing revenue generation.